USING ENGLISH TO ENHANCE THE ELEMENTARY SCHOOL STUDENTS’ SENSE OF NATIONALISM - Achmad Fanani (Universitas Pesantren Tinggi Darul Ulum Jombang, 2015)
English is an international language and is used worldwide. Hence, it must be mastered by anyone who would like to interact and succeed internationally. Learning English is very important to do since early ages (more specifically since elementary school) to have better result. Unfortunately the government has made unpopular decision by removing English subject from the elementary school curriculum because of its potential to reduce the students’ sense of nationalism. In fact, there is no scientific evidence that prove learning English in early age can only reduce the students’ sense of nationalism. Indonesian people have been for long time dealing with foreign languages such as Arabic, Dutch, and Japanese. But the nationalism of Indonesian people in general remains high. In short, there is no need to remove this subject from the curriculum. Teaching English is actually can be used to raise the sense of nationalism. At least there are two ways that can be applied: internalization of nationalism values into the teaching materials and using songs of nationalism. Through these techniques it is expected that not only the children’s English but also their sense of nationalism will increase. Keywords: English, nationalism, internalization of values, nationalism songs Abstrak Bahasa Inggris adalah bahasa internasional dan digunakan di seluruh dunia. Oleh karena itu, ia harus dikuasai oleh siapapun yang ingin berinteraksi dan meraih kesuksesan secara internasional. Belajar bahasa Inggris sangat penting dilakukan sejak usia dini (lebih khusus lagi sejak SD) agar hasilnya lebih baik. Sayangnya pemerintah telah membuat keputusan yang tidak populer dengan menghapus pelajaran bahasa Inggris dari kurikulum sekolah dasar karena berpotensi mengurangi rasa nasionalisme siswa. Padahal, tidak ada bukti ilmiah yang membuktikan pembelajaran bahasa Inggris di usia dini bisa mengurangi rasa nasionalisme siswa. Orang Indonesia telah lama berurusan dengan bahasa asing seperti bahasa Arab, Belanda, dan Jepang. Tapi nasionalisme masyarakat Indonesia pada umumnya tetap tinggi. Singkatnya, tidak perlu mengeluarkan mata pelajaran Bahasa Inggris dari kurikulum. Pengajaran bahasa Inggris sebenarnya bisa digunakan untuk meningkatkan rasa nasionalisme. Setidaknya ada dua cara yang bisa diterapkan: internalisasi nilai nasionalisme ke dalam bahan ajar dan menggunakan lagu nasionalisme. Melalui dua cara ini diharapkan tidak hanya bahasa Inggris anak-anak yang meningkat tetapi juga rasa nasionalisme mereka. Kata kunci: bahasa Inggris, nasionalisme, internalisasi nilai, lagu nasionalisme